#TITLE_ALTERNATIVE# - Darjanto (NIM:250.92.047), Helmy
Abstract: Field observations show that dynamic response of foundations exhibits non-linear behaviour. Non-linearity of the dynamic response of foundation is caused by contact effects that can be found in the form of (1) slip or (2) prestressing. This non-linearity may dictate the amount of vibration amplitude and may be aproximated by using a weak zone or strong zone in order to model slip (gap) or backfill compaction. Analysis for the weak zone and the strong zone is performed by utilizing Novak s theory. The theory is developed for simulating a contact effect and by assuming that soil is a viscoelastic medium. It is numerically solved through the finite element analysis. Dynamic parameters that area required in order to model the contact effects include : thickness, shear modulus, damping and Poisson s ratio of the weak zone or strong zone. Analysis using weak zone or strong zone is verified by results of full scale tests perfomed by Gle (1981). He observed that non-linear behaviour from soil-pile interaction occured during laterally dynamic loading.